Sludge: next paradigm for enzyme extraction and energy generation. Issue 2 (7th February 2019) - Karn, Santosh Kumar; Kumar, Awanish
Abstract: Excess of sludge generated during activated sludge process by various industries is causing sludge disposable problem worldwide. Sludge contains organic materials of a highly complex mixture of molecules with some toxic compounds. Thus, the harmful effect of sludge could be managed by processing of sludge and recovery of useful products. Sludge could undergo biodegradation and used for the recovery of enzymes and energy. Enzymes (amylase, alkaline phosphatase, lipase, proteases) are produced by microorganisms and released into the media to degrade organic matters of sludge. These enzymes can be extracted by means of different physical and chemical methods from activated sludge for the multifarious application. Current manuscript discussed all the methods utilized for the extraction of enzyme and their utilization in terms of energy generation. Extracted industrial enzymes are used in agriculture, dairy, detergents, pulp, paper, cosmetics, and pharmaceutics. Apart from enzyme extraction, production of energy (biofuels, electricity) is also done by key treatment of sludge. It is a compilation of current knowledge and expected competitiveness with respect to existing methods already applied in practice for enzyme recovery. This paper presents an overview of the production of valuable enzymes and various forms of energy from sludge, which is toxic and unwanted for life.